Education for a Democratic Society. - Ryder, John. (Value Inquiry Book Series, 2007)
This book is the third volume of selected papers from the Central European Pragmatist Forum (CEPF). It deals with the general question of education, and the papers are organized into sections on Education and Democracy, Education and Values, Education and Social Reconstruction, and Education and the Self. The authors are among the leading specialists in American philosophy from universities across the U.S. and in Central and Eastern Europe. The series Studies in Pragmatism and Values promotes the study of pragmatism's traditions and figures, and the explorations of pragmatic inquiries in all areas of philosophical thought.